Can an Increase in Public Investment Sustainably Lift Economic Growth? - Mourougane, Annabelle (OECD Publishing, 2016)
This paper seeks to identify the conditions under which raising public investment can sustainably lift growth without deteriorating public finances. To do so, it relies on a range of simulations using three different macro-structural models. According to the simulations, OECD governments could finance a ½ percentage point of GDP investment-led stimulus for three to four years on average in OECD countries without raising the debt-to-GDP ratio in the medium term, provided projects are sound. After one year, the average output gains for the large advanced economies of such a stimulus amount to 0.4-0.6%. However, the gains are particularly uncertain for Japan. Reprioritising spending in later years would lead to average long-term output gains of between 0.5 to 2% in the large advanced economies. Those gains depend on the assumptions made on the rate of return. Hysteresis reinforces the case for an investment-led stimulus. Output gains will also be higher if the stimulus is combined with structural reforms and if countries act collectively
Keywords: Economics